Sam Hughes and Mobilization of Canadian Volunteers for War (August 1914 — October 1915) - E. S. Symonenko (Научный диалог, 2021)
The process of mobilization of Canadian volunteers, carried out by the Minister of Militia Sam Hughes during the First World War, is considered. The chronological framework is limited by the dates of Canada’s entry into the war (August 4, 1914) and the end of the active phase of the mobilization of Canadian volunteers (October 1915) in connection with the first symptoms of the army manning crisis. The relevance of the study is due to insufficient knowledge of the specifics of Canada's mobilization activity during the First World War. For the first time, ideas are formulated and the activities of the Minister of Militia S. Hughes in the process of mobilizing Canadian troops during the war years are analyzed. The sources for the study were Canadian historical and statistical collections, as well as a collection of official documents of the Canadian government and publications of the Canadian federal and provincial press for two military years (1914—1915). The article traces the views of S. Hughes on the issue of Canada's participation in the war and his activities in the field of recruiting the volunteer army (1914—1915). It is proved that the decisive character of S. Hughes and the authoritarian style of his leadership predetermined the nature of the Canadian mobilization. In fact, it got out of the control of the British authorities due to the minister's refusal from the official mobilization plan, which provided for a too slow pace of manning. Thus, the personal efforts of S. Hughes to organize the process of mobilization contributed to its complete success.